Evaluation of the use of a parent questionnaire to provide later health status data: the PANDA study. Issue 4 (12th October 2015) - Field, David; Spata, Edi; Davies, Thomas; Manktelow, Brad; Johnson, Samantha; Boyle, Elaine; Draper, Elizabeth S
Abstract : Background: Routine comparable outcome data collection relating to the later health status of babies born very preterm has long been considered important, but has not been achieved in the UK. Aim: To test the potential for a parental questionnaire to provide these data for all eligible babies from a geographical population. Methods: Consent for follow-up by questionnaire (using the Parent Report of Children's Abilities-Revised combined with questions derived from the Oxford minimum dataset) was sought for all babies ≤30 weeks of gestation, discharged from a hospital in the East Midlands and Yorkshire regions of the UK, having been born between 1 January 2007 and 31 December 2011. Results: The rate of consent to participate in follow-up showed a steady increase over time to 83.1% in 2011. However, the response rate in terms of completion and return of the questionnaire at 2 years, as a proportion of those eligible, showed little change over time, varying between 42% and 46%. Among those children where a questionnaire was returned, the rate of disability was broadly consistent over time: lowest in 2009, 21.0% (95% CI 16.8% to 25.6%) and highest in 2011, 25.5% (95% CI 21.5% to 31.2%). The instruments used appeared effective with the capability of discriminating between children with physical and/or cognitive disability. Conclusions: The overall response rate in terms of returned questionnaires was disappointing and inadequate to recommend for implementation. It is possible that response rates would have been higher had clinical follow-up been linked to the data obtained from the questionnaires rather than running as a parallel process.